Transport Phenomena Practice
Transport Phenomena Practice
Transport Phenomena Practice
ii) Provide full and clear derivations and justifications of your work
iii) In case a shell balance is required or needed, show the control volume clearly
1. Estimate the diffusivity DAB (in cm2 /s) of H2 (A) in Argon (B) at 2.6310-4 atm and
527oC using Eq. 17.3-12.
Given,
T= 800.15 K
ρ= 2.6310-4 atm
√
𝒟AB¿ 0.0018583 T 3(
1
+
1
)
1
M A M B ρ . Ω D AB(σ AB)2
1
𝒟AB¿ 0.0018583 √(800.15)3 ¿ ¿ ) 2
(2.63 10−4)(0.7202)(3.1735 )
𝒟AB=
2. An isothermal second order chemical reaction occurs in a plug flow reactor (PFR).
A D. A is present in small amounts in B. The inlet concentration is C A0, and the
flow is to be treated as piston flow with a uniform velocity profile v. The binary mass
diffusivity is represented as 𝒟AB.
a) Neglecting diffusion and using a shell balance, show that the concentration profile
satisfies.
Consider a small shell with thickness Δz and cross-sectional area A, located at a distance z
along the plug flow reactor (PFR).
The control volume is the small shell with thickness Δz and cross-sectional area A. It is
positioned at a distance z along the reactor.
The shell balance equation relates the rate of change of A concentration within the control
volume to the net flow of A in and out of the control volume, as well as the chemical reaction
rate.
Rate of accumulation = Net flow in - Net flow out + Generation by reaction
The rate of accumulation of A within the control volume is given by:
Rate of accumulation = Δ (A * V) / Δt
Since we assume steady-state operation, the rate of accumulation is zero:
Rate of accumulation = 0
The net flow in of A into the control volume is due to the axial flow velocity v and the
concentration of A at the inlet (CAO):
Net flow in = v * CAO * A
The net flow out of A from the control volume is due to the axial flow velocity v and the
concentration of A at the outlet (CA):
Net flow out = v * CA * A
The generation of A by the chemical reaction is given by the rate equation for the second-
order reaction:
Generation by reaction = - k m CA2 * A
Here, k m is the rate constant for the reaction.
By substituting the expressions into the shell balance equation (Rate of accumulation = Net
flow in - Net flow out + Generation by reaction) and rearranging the terms,
0 = v * CA0 * A - v * CA * A - k m CA2* A
0 = v * (CA0 - CA) * A - k m CA2* A
Divide both sides of the equation by A:
0 = v * (CA0 - CA) - k m CA2
Rearrange the terms and divide both sides of the equation by v:
v * dCA/dz = -k m CA2
∫ dCA / CA2= -k / v ∫ dz
-CA (-1) = -k / v ∫ dz
-CA (-1) = -k / v z + C
Where C is the constant of integration. Rearranging the equation to solve for CA:
CA (-1) = k / v z - C
1 / CA = v / k z - C'
Where C' = 1 / C is another constant of integration. Rearranging the equation to solve for CA:
CA = 1 / (v / k z - C')
CA(z) = 1 / (v / k z - C')
Where v is the velocity, k is the rate constant for the reaction, and C' is the constant of
integration.
3. A solid sphere of radius a is immersed in a quiescent liquid enclosed in an
impermeable spherical container of radius R. A homogeneous chemical reaction ( A
D ) of order 0, and of constant k m ( RA km ) occurs in the solution. The
solubility of A in the solution is assumed small and denoted as c A0 , and the binary
mass diffusivity as 𝒟AB (in which B denotes the solvent). Consider the steady state
problem.
a) Using a shell balance, prove the following equation 𝒟AB * (1/r2) * d/dr (r2 (dcA/dr))
= km
Consider a control volume in the form of a spherical shell within the liquid, with a radius r
and thickness Δr. The outer radius of the shell is r + Δr/2, and the inner radius is r - Δr/2.
By assuming a steady state, the accumulation term is negligible so need to focus on the
generation term. The generation term represents the rate of consumption of species A (cA) and
is given by -km cA.
To relate the concentration of species A (cA) to the concentration of species D (c D), let's
assume that the concentration of D, cD, is negligible compared to the solubility of A in the
solution, cAO. Therefore, cA ≈ cAO.
Using the rate of reaction equation,
RA = -km, we have - km = - km * cAO.
Equating the generation term to the accumulation term:
- km * cAO = Accumulation
The accumulation term can be written as:
Accumulation = 4πr2 * 𝒟AB * (1/r2) * d/dr (r2 * (dcA/dr))
Simplifying the equation and canceling out common terms,
𝒟AB * (1/r2) * d/dr (r2 (dcA/dr)) = km
a) Show that θ=T-Ts satisfies ∂θ/∂τ=1/ξ^2. ∂/∂ξ (ξ^2. ∂θ/∂ξ) where ξ=r/R and τ=α.t/R^2
where α is the thermal diffusivity, ρ is the density, and Cp is the specific heat capacity at
constant pressure.
Since Ts is the steady-state temperature profile, it does not change with time (∂T s /∂t = 0).
Therefore, the equation becomes:
So,
∂θ/∂τ = α * (1/ (R2* ξ2)) * ∂/∂ξ (ξ2* ∂θ/∂ξ) + Sv / (ρ * Cp)
∂θ/∂τ = 1/ (ξ2) * ∂/∂ξ (ξ2* ∂θ/∂ξ)
Therefore, θ = T - Ts satisfies the equation:
At ξ=0;
The original temperature profile equation in terms of θ:
At ξ = 0 (corresponding to r = 0): The condition for θ when ξ approaches 0. From the original
definition of ξ = r/R, as r approaches 0, ξ approaches 0. Therefore,
Θ (0, τ) = T (0, t) - Ts (0) = T (0, t) - Ts(0) = 0 - Ts(0) = -Ts(0)
At ξ=1;
q = -k * A * (∂T/∂r)
where q is the heat flux, k is the thermal conductivity, A is the surface area, and (∂T/∂r) is the
temperature gradient in the radial direction.
Substituting T = θ + Ts,
q = -h * (θ + Ts - T∞)
Substituting T = θ + Ts,
(∂θ/∂ξ) = (∂ (θ + Ts)/∂r) * R
= (∂θ/∂r) * R [since (∂Ts/∂r) = 0]
At ξ = 1, (∂θ/∂ξ) = (∂θ/∂r) * R, and from the heat flux expression that q = -h * (θ + Ts - T ∞).
Therefore, at ξ = 1,
(∂θ/∂ξ) = -h * (θ - T∞) / k
c) Show that θ=T-Ts is given by θ=Σ (An.Φn (ξn, λn) exp (-λn2.τ) where n=1 to n=∞
By using equation, ∂θ/∂τ = (1/ξ2) ∂/∂ξ (ξ2∂θ/∂ξ)
Define a separation of variables solution as follows:
θ = Φ(ξ)T(τ)
Substituting this into the equation and dividing both sides by Φ (ξ)T(τ),
(1/ξ2) d/dξ (ξ2 dΦ/dξ) = (1/T) dT/dτ
Since both sides are equal to a constant,
(1/ ξ2) d/dξ (ξ2 dΦ/dξ) = -λ2 (1) and
(1/T) dT/dτ = λ2 (2), where λ is the constant.
Equation (1),
d/dξ (ξ2 dΦ/dξ) = -λ2 ξ2
d2Φ/dξ2 + (λ2 - 2/ξ2) Φ = 0
This is a standard differential equation, and the general solution is given by Bessel's equation.
Φ(ξ) = C1 J0(λξ) + C2 Y0(λξ) (3)
where J0(λξ) and Y0(λξ) are Bessel functions of the first and second kind, respectively.
Equation (2) for T(τ):
(1/T) dT = λ2 dτ
Integrating both sides gives:
ln(T) = λ2 τ + C3
where C3 is a constant of integration. Taking the exponential of both sides,
T = C4 exp (λ2 τ) (4)
where C4 = exp(C3).
Now, combining Equations (3) and (4),
θ = Φ(ξ)T(τ) = (C1 J0(λξ) + C2 Y0(λξ)) (C4 exp (λ2 τ))
θ = C1C4 J0(λξ) exp (λ2 τ) + C2C4 Y0(λξ) exp (λ2 τ)
Since λ is a constant, combine C 1C4 and C2C4 into new constants an = C1C4 and Bn = C2C4,
respectively. Therefore,
θ = Σ (An J0(λnξ) + Bn Y0(λnξ)) exp (λn2 τ)
The Bessel function Y0(λξ) is unbounded as ξ approaches zero, which is physically unrealistic
for the temperature profile. Therefore, we can assume that C2 = 0, leading to:
θ = C1C4 J0(λξ) exp (λ2 τ)
Express the Bessel function J0(λξ) in terms of Eigen functions and eigenvalues. as:
J0(λξ) = Σ (An Φn (ξ, λn))
where Φn (ξ, λn) represents the Eigen functions associated with the eigenvalues λn, and An
are constants to be determined.
Substituting this back into the expression for θ,
θ = C1C4 Σ (An Φn (ξ, λn)) exp (λ2 τ)
Since the sum and the exponential term do not depend on ξ, we can interchange the
summation and the exponential term:
θ = Σ (An Φn (ξ, λn) exp (λ2 τ)) (1)
where now Φn (ξ, λn) and An are given by:
Φn (ξ, λn) = J0(λnξ)
An = C1C4
Replace λ2 with λn2,
θ = Σ (An Φn (ξ, λn) exp (-λn2 τ)) (2), where n=1 to n=∞
where Φn (ξ, λn) = J0(λnξ) and An = C1C4.
Find an expression for Φn (ξ, λn) and write an equation satisfied by the eigenvalues λn.
The Eigen functions Φn (ξ, λn) can be expressed in terms of the Bessel function of the first
kind, denoted as Jν(z), Φn (ξ, λn) = J0(λnξ)
Substitute the separation of variables solution into the original partial differential equation:
∂θ/∂τ = (1/ξ2) ∂/∂ξ (ξ2 ∂θ/∂ξ)
By substituting θ = Φ(ξ)T(τ) and dividing both sides by Φ (ξ)T(τ),
(1/ξ2) d/dξ (ξ2 dΦ/dξ) = (1/T) dT/dτ
(1/ξ2) d/dξ (ξ2 dΦ/dξ) = -μ2
Where μ^2 represents the constant eigenvalue associated with the Eigen function Φn (ξ, λn).
In this case, since we have ν = 0, the Eigen functions Φn (ξ, λn) are given by:
d) The initial temperature is T0. Give an expression for the An coefficients as a function
of T0 and Ts.
The expression for θ as:
θ = Σ (An Φn (ξ, λn) exp (-λn2 τ))
At time τ = 0, the unsteady-state temperature profile is equal to the initial temperature,
Θ (ξ, τ=0) = T0
Substituting the expression for θ and setting τ = 0,
Σ (An Φn (ξ, λn) exp (-λn2 * 0)) = T0
Since exp (0) = 1,
Σ (An Φn (ξ, λn)) = T0
By considering the steady-state temperature profile, denoted as Ts. In the steady state, the
rate of heat generation Sv is balanced by the heat transfer through the boundary, resulting in a
constant temperature distribution. This means that θ = T - Ts = 0,
Σ (An Φn (ξ, λn) exp (-λn2 τ)) = Ts
Σ (An Φn (ξ, λn) exp (-λn2 τ)) - Ts = 0
Σ (An Φn (ξ, λn) exp (-λn2 τ)) = Ts
Since the expression holds for all values of τ, each term in the summation must individually
equal zero:
An Φn (ξ, λn) exp (-λn2 τ) = 0
As exp (-λn2 τ) is non-zero,
An Φn (ξ, λn) = 0
Since Φn (ξ, λn) ≠ 0 for a valid Eigen function, we can conclude that the coefficient An must
be zero:
An = 0
Therefore, the coefficients An are determined to be zero for all n. This implies that the initial
condition T0 and the steady-state temperature Ts do not contribute to the series expansion of
θ, and the expression becomes:
θ=0
This indicates that the unsteady-state temperature profile is identically zero in this case.